2008
DOI: 10.1136/jmg.2008.058909
|View full text |Cite
|
Sign up to set email alerts
|

The CTG repeat expansion size correlates with the splicing defects observed in muscles from myotonic dystrophy type 1 patients

Abstract: The CTG repeat length plays a key role in the extent of splicing misregulation and foci formation, thus providing a useful link between the genotype and the molecular cellular phenotype in DM1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 25 publications
3
46
1
2
Order By: Relevance
“…8 To assess the in trans effect of the CTG repetition on the splicing regulation in DM1 differentiating myoblasts, we analyzed the expression of IR and MBNL1 gene isoforms at different times of differentiation (stages T0, T4 and T10). RT-PCR amplification showed that in DM1 cells the ratios of the IR-A/TOT ( Figure 2b Catabolic pathways in DM1 muscle cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…8 To assess the in trans effect of the CTG repetition on the splicing regulation in DM1 differentiating myoblasts, we analyzed the expression of IR and MBNL1 gene isoforms at different times of differentiation (stages T0, T4 and T10). RT-PCR amplification showed that in DM1 cells the ratios of the IR-A/TOT ( Figure 2b Catabolic pathways in DM1 muscle cells.…”
Section: Resultsmentioning
confidence: 99%
“…RNA fluorescence in situ hybridization was performed as described. 8 TUNEL and cytochrome c release detection. Apoptosis detection in 0-, 4-, 10-and 15-day myotubes was performed using TUNEL and cytochrome c release assays.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1A, and contains the open reading frame of lacZ, 24 MS2 stem-loop sequences, and the 3ЈUTR of DMPK containing either five or 145 CUG-triplet repeats (lacZ-MS2-5CUG or lacZ-MS2-145CUG). Although five CUG repeats are insufficient to promote RNA aggregation, 145 CUG repeats are known to promote RNA foci formation in DM1 patients (Botta et al, 2008). We chose this CUG-repeat expansion size so that the transcripts would not all be aggregated and we would be able to detect and track single CUG-rich mRNAs (see below).…”
Section: The Ms2-gfp System For Visualization Of Transcripts In Livinmentioning
confidence: 99%